Char derived from sewage sludge of hydrothermal carbonization and supercritical water gasification Comparison of the properties of two chars - Wang, Chenyu (Waste management (New York, N.Y.), 2021)
Copyright © 2021 Elsevier Ltd. All rights reserved.